Pancreatic ductal adenocarcinoma subtyping using the biomarkers hepatocyte nuclear factor-1A and cytokeratin-81 correlates with outcome and treatment response - Muckenhuber, Alexander; Berger, Anne Katrin; Eils, Roland; Stenzinger, Albrecht; Jäger, Dirk; Springfeld, Christoph (Clinical cancer research, 2018)
Purpose: Pancreatic ductal adenocarcinoma (PDAC) is associated with a dismal prognosis and poor therapeutic response to current chemotherapy regimens in unselected patient populations. Recently, it has been shown that PDAC may be stratified into functionally and therapeutically relevant molecular subgroups and that some of these subtypes can be recapitulated by IHC for KRT81 [quasi-mesenchymal (QM)/squamous/basal-like] and HNF1A (non-QM, overlap with exocrine/ADEX subtype). Experimental Design: We validated the different outcome of the HNF1A/KRT81 PDAC subtypes in two independent cohorts of surgically treated patients and examined the treatment response to chemotherapy in a third cohort of unresectable patients. The first two cohorts included 262 and 130 patients, respectively, and the third independent cohort comprised advanced-stage PDAC patients who were treated with either FOLFIRINOX (64 patients) or gemcitabine (61 patients). Results: In both cohorts with resected PDAC, the HNF1A-positive subtype showed the best, the KRT81-positive subtype the worst, and the double-negative subtype an intermediate survival (P < 0.013 and P < 0.009, respectively). In the chemotherapy cohort, the survival difference between the double-negative and the HNF1A-positive subtype was lost, whereas the dismal prognosis of KRT81-positive PDAC patients was retained (P < 0.021). Patients with a KRT81-positive subtype did not benefit from FOLFIRINOX therapy, whereas those with HNF1A-positive tumors responded better compared with gemcitabine-based treatment (P < 0.038). Conclusions: IHC stratification recapitulating molecular subtypes of PDAC using HNF1A and KRT81 is associated with significantly different outcomes and responses to chemotherapy. These results may pave the way toward future pretherapeutic biomarker-based stratification of PDAC patients. Clin Cancer Res; 24(2); 351-9. ©2017 AACR.